Overestimation of evapotranspiration across India if not considering the impact of rising atmospheric CO2 - Surendran, Sruthi; Sunil, Nandhana; Pahari, Tanushri; He, Yufeng; Jaiswal, Deepak (Frontiers in Water, 2025)
Evapotranspiration (ET), a key component of the hydrological cycle, responds to and influences climate change, making accurate estimation of reference ET (ETo) critical for long-term impact assessments. The widely applied FAO Penman–Monteith (FAO-PM) equation for calculating ETo does not account for rising atmospheric CO2, which reduces vegetation stomatal conductance and can lead to systematic overestimation of ETo. We derived a modified FAO-PM equation incorporating CO2 effects on stomatal behavior. Using projections from five global circulation models, we compared spatiotemporal average of ETo estimates for India from the original and modified equations under SSP5-8.5 and SSP1-2.6. Differences were 0.11–1.29 mm day−1 (2021–2030), 0.09–1.90 mm day−1 (2051–2060), and 0.17–3.14 mm day−1 (2091–2100) under SSP5-8.5, with slightly lower values under SSP1-2.6. Seasonal differences between the predicted ETo from the two equations peaked during the pre-monsoon, reaching 3.90 mm day−1 (SSP5-8.5) and 1.74 mm day−1 (SSP1-2.6). Neglecting stomatal responses to CO2 could lead to ETo overestimation of ~29% under SSP5-8.5 by 2100, potentially biasing projections of droughts, heatwaves, and water demand. By contrast, overestimation is moderate (~13%) under SSP1-2.6. Incorporating the impact of CO2 into ETo estimation is therefore essential for robust climate change impact assessments.